Validity and reliability of a test used for assessing university students’ academic language proficiency - Mezzadri, Marco (Educazione Linguistica Language Education, 2018)
This article presents a test model developed to assess university students’ academic language proficiency. The context is that of Italian universities, which are required by law to assess first year students’ initial preparation. Drawing on the literature regarding test construct, it explores the validity and reliability of the test through the analysis of the data collected during an experimental implementation phase carried out at the Universities of Genova, Parma and Urbino.